2013
DOI: 10.1111/gcb.12243
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to a metal under global warming is shaped by thermal adaptation along a latitudinal gradient

Abstract: The increase in temperature as consequence of the recent global warming has been reported to generate new ice-free areas in the Antarctic continent, propitiating the colonization and spread of plant populations. Consequently, antarctic vascular plants have been observed extending their southern distribution. But as the environmental conditions toward southern localities are progressively far apart from these species' physiological optimum, the colonization of new sites and ecophysiological responses could be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 88 publications
(56 citation statements)
references
References 55 publications
0
53
1
Order By: Relevance
“…In contrast to current findings, warming imposed higher predation rates of I. elegans on Artemia nauplii (Dinh Van et al. , ), and on Daphnia magna water fleas (De Block et al. ).…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…In contrast to current findings, warming imposed higher predation rates of I. elegans on Artemia nauplii (Dinh Van et al. , ), and on Daphnia magna water fleas (De Block et al. ).…”
Section: Discussioncontrasting
confidence: 93%
“…Growth rates of both mosquito and damselfly larvae were calculated as (ln final mass −ln initial mass )/5 days (Dinh Van et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…This became evident not only by lower levels of the measured fitness trait (intrinsic growth rate), but also in the lower RNA:DNA ratio and lower sugar content when Daphnia were exposed to nZnO at 24°C than at 20°C. A higher toxicity of trace metals under warming has been documented in the study species (Kimberly & Salice, 2014) as well as in other aquatic invertebrates (Debecker, Dinh, & Stoks, 2017; Dinh et al., 2013). In contrast, interaction effects between warming and nanocontaminants have been rarely studied.…”
Section: Discussionmentioning
confidence: 99%
“…This resembles the long‐term evolutionary pattern where cold‐adapted high‐latitude populations of the damselfly I. elegans are more sensitive to zinc at 24°C compared to 20°C (hence a synergism), while warm‐adapted low‐latitude populations are not (Dinh et al., 2013). Synergisms between contaminants and environmental variables are expected when the environmental variable itself imposes stress (Liess et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…While the idea of context‐dependent responses is well established in ecology (Cardinale et al ., ; Nowlin & Drenner, ), it has received little attention in ecotoxicology (Clements, Hickey & Kidd, ; Dinh Van et al ., ; Merriam et al ., ). Previous studies have shown that the effects of pesticides on aquatic communities may depend on the types of predators present (Relyea, Schoeppner & Hoverman, ) and initial community composition (Rohr & Crumrine, ), suggesting that the concept of context dependency can be extended to include variation in responses of communities to contaminants and other anthropogenic stressors (Table ).…”
Section: Introductionmentioning
confidence: 98%